ESTIMASI NILAI PEMULIAAN UKURAN TUBUH PADA PEJANTAN SAPI ACEH ( Bos indicus ) UMUR 550 HARI - Widya Pintaka Bayu Putra; Hendra Saumar (Universitas Tribhuwana Tunggadewi, 2018)
Body measurements are one of livestock selection criteria for breeds standardization. This research was carried out to select the best sire at BPTU-HPT Sapi Aceh Indrapuri through body measurements at 550 days of age. Records data of livestock from 2010-2013 were used in this study and consisted of chest girth (CG), withers height (WH) and body length (BL). The average of body measurements were 105.22+6.06 cm (CG), 88.42+4.37 cm (WH) and 83.03+4.74 cm (BL). The heritability (h2) estimation were ranged from medium (CG and WH) to high (BL) criteria. Higher of standard error (SE) than h2 values was indicated that the data in this study was less and the h2 values were not accurate. The cumulative breeding value (BV) of body measurements were reached from -3.69 (Sire: A.004) to +3.89 (Sire: P.0751). Ranking of sire based on BL were not accurate because of lower relative accuracy (RA) value than 1.00 in one of tested sires.